A Comprehensive Review on the Impact of Edible Coatings, Essential Oils, and Their Nano Formulations on Postharvest Decay Anthracnose of Avocados, Mangoes, and Papayas - Sivakumar, Dharini; Tuna Gunes, Nurdan; Romanazzi, Gianfranco (Frontiers in Microbiology, 2021)
Subtropical fruit such as avocados (Persea americana), mangoes (Mangifera indica L.), and papayas (Carica papaya L.) are economically important in international trade and predominantly exported to the Europe. Theses fruits are highly consumed due to their health benefits. However, due to long distance shipping and time required to reach the retail department stores, post-harvest losses, due to postharvest decay occur during the supply chain, affect the fruit quality on arrival at the long-distance distribution points. Currently, the use of synthetic fungicides, such as Prochloraz®, at the packing line are to reduce decay and retain the overall quality of mangoes and avocados. Due to the ban imposed on the use of synthetic fungicides on fresh fruit, several studies have focused on the development of alternative technologies to retain the overall quality during marketing. Among the developed alternative technologies for commercial adoption is the use of edible coatings, such as chitosan biocontrol agents and essential oil vapors. The objective of this review is to summarize and analyze the recent advances and trends in the use of these alternative postharvest treatments to maintain the overall fruit quality of avocado, mangoes and papayas.